2001
DOI: 10.1021/ac010436c
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Individual Particle Atomic Composition by Aerosol Mass Spectrometry

Abstract: Advances in instrumentation used for particle compositional analysis have enabled real-time identification and classification of individual particles. However, precise quantitation of individual particle compositions has been elusive. Here, we demonstrate that real-time quantitative single-particle compositional analysis is possible. This is illustrated for individual particles of sodium chloride (70 nm), ammonium sulfate (70 nm), and silica (40-2000 nm) using a real-time aerosol mass spectrometer. Atomic frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…Differences in power density have been shown to affect the mass spectral patterns produced. For example, Reents and Schabel (2001) found that variation in peak power density, achieved by varying the 193 nm laser power setting, resulted in variations in the sodium fraction reported in the mass spectra of NaCl. The effect of different laser power settings on the distribution of τ values for kaolinite sample KGa-1b and illite NX is shown in Fig.…”
Section: The Effect Of Laser Power Settingmentioning
confidence: 99%
“…Differences in power density have been shown to affect the mass spectral patterns produced. For example, Reents and Schabel (2001) found that variation in peak power density, achieved by varying the 193 nm laser power setting, resulted in variations in the sodium fraction reported in the mass spectra of NaCl. The effect of different laser power settings on the distribution of τ values for kaolinite sample KGa-1b and illite NX is shown in Fig.…”
Section: The Effect Of Laser Power Settingmentioning
confidence: 99%
“…Most of these new devices are limited to obtaining atomic, rather than molecular, composition of the aerosol. These devices usually employ high power lasers (Reents and Schabel 2001) and plasmas (Okada et al 2002) to desorb and ionize aerosol smaller than 20 nm in diameter. Another class of instruments infers the chemical composition of ultrafine aerosol indirectly by measuring their growth behavior in a saturated vapor (Saros et al 1996;Rader and McMurry 1986) or volatility in a temperature-controlled environment .…”
Section: Introductionmentioning
confidence: 99%
“…The many complexities associated with the combined desorption and ionisation process result in the limitation that for most LDI instruments, the chemical composition data derived from sampling ambient particles are mainly qualitative in nature. If enough laser energy to cross the plasma formation threshold can be delivered, the Particle Blaster can deliver quantitative data on the elementary compositions of particles, as all the atoms present are converted to positive ions (Reents & Ge, 2000;Reents & Schabel, 2001). A similar quantitative method was also demonstrated by Mahadevan et al (2002).…”
Section: Single-step Laser Methodsmentioning
confidence: 99%